Um sistema de monitoramento para caracterização de algoritmos distribuídos - Fachini, Elizeu Elieber (2016)
Monitoring is the act of collecting information concerning the characteristics and status of resources of interest. It can be used to the management and allocation of resources, detection and correction of failures and also to the evaluation of performance parameters. To automatically accomplish the monitoring a tool is needed that has functionalities related the acquiring, processing, distributing and presenting of monitoring events. In this work we are interested in a monitoring system to give support to the experimental execution of distributed algorithms, with the objective of correlating the device status with the execution data and, this way, make possible an analysis of cluster resources used by the application. Then, it’s needed a tool with particular characteristics, such as the ability to collect data with a small time period, with low intrusiveness and making the full data available. As was not possible find in the literature a tool with the features required, we developed a new monitoring tool named MSPlus. The features of this tool were evaluated through experiments with the isolated tool and comparing it with other tool. Additionally, we apply the tool in a distribucted system to monitor a distribucted algorithm.